2006
DOI: 10.1111/j.1540-8159.2006.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Insufficiency and the Risk of Infection from Pacemaker or Defibrillator Surgery

Abstract: Renal insufficiency dramatically increases the risk of infection complicating pacemaker or ICD surgery. This association should be part of the risk-benefit consideration prior to device implantation. Additional study of more extensive perioperative antibiotic therapy in this subset of patients is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
164
2
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(180 citation statements)
references
References 19 publications
6
164
2
8
Order By: Relevance
“…4 However, to our knowledge, few of these studies have investigated the risk factors for infection by means of a casecontrol study. 6 We give a detailed account of an infection control investigation and the risk factors associated with the development of SSI in patients who received pacemakers and ICDs. In brief, the infection investigation found that aspects of preoperative skin preparation and antibiotic prophylaxis, and procedures involving an in situ abdominal device, were significantly associated with subsequent infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, to our knowledge, few of these studies have investigated the risk factors for infection by means of a casecontrol study. 6 We give a detailed account of an infection control investigation and the risk factors associated with the development of SSI in patients who received pacemakers and ICDs. In brief, the infection investigation found that aspects of preoperative skin preparation and antibiotic prophylaxis, and procedures involving an in situ abdominal device, were significantly associated with subsequent infection.…”
Section: Discussionmentioning
confidence: 99%
“…Reported risk factors for infection include congestive heart failure, diabetes mellitus, renal insufficiency and the frequency with which generators are exchanged. 6 The experience level of the person inserting the device has also been shown to influence the risk of infection. 7 Overall infection rates for implantable cardiac device procedures have been reported to be in the range of 0.5%-5.1%.…”
mentioning
confidence: 99%
“…Each biopsy specimen demonstrated histologic evidence of NSF, lending validity to our skin scoring system. We intentionally limited our analysis for NSF to a noninvasive skin examination so as to maximize the number of patients who would participate and to avoid the less than trivial infectious complications of a full-thickness (often lower extremity) skin biopsy (20,21), especially given that the patients in this study universally had renal failure and a high prevalence of skin fibrosis and diabetes mellitus, which are known risk factors for surgical wound infection and poor wound healing (22)(23)(24). By not requiring a skin biopsy, we were able to achieve a 94% participation rate and to minimize selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with moderate to severe renal disease exhibit higher device infection rates as compared to the general population [24][25][26]. Cardiac device infection can be a potentially life-threatening if untreated and can also lead to endocarditis [27,28].…”
mentioning
confidence: 99%
“…For these reasons, the transvenous route has become the most frequently used method for implantation of CIEDs. However, the use of the transvenous CIEDs can be associated with significant complications in chronic HD patients including central venous stenosis, tricuspid regurgitation (TR), and device infection [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
mentioning
confidence: 99%